Efficacy of Transversus Thoracic Muscle Plane Block for Analgesia After Pediatric Cardiac Surgery - Parajuli, Santosh Sharma; Shrestha, Suman; Shrestha, Binish Man (Nepalese Heart Journal, 2025)
Background: The perioperative pain management plays a key role in the management of patients undergoing pediatric cardiac surgery. We studied the effect of transversus thoracic muscle plane block (TTPB) on acute postoperative pain and 24 hours opioids consumption in pediatric cardiac surgical patients. Methods: Patients in whom transversus thoracic muscle plane catheter was placed were kept in one group and in the other group patients who were given conventional medicines for pain management were kept. The primary study end point was to compare the consumption of fentanyl and to assess FLACC pain scale in postoperative period in the first 24 hours post extubation in both groups. Results: The 24 hours fentanyl consumption was 8.00 +/- 5.49 micrograms in transversus thoracic muscle plane group and 32.20 +/- 10.53 micrograms in the control group in the first 24 hours postoperatively which was statistically significant (p <0.001). The FLACC score was also significantly lesser in the TTPB group compared to the control group in the first 24 hours postoperatively. Conclusion: Transversus thoracic plane block is superior to the conventional opioid injection method for postoperative pain management in pediatric cardiac surgical patients.